Hydrolysis of scandium alkyl derivatives supported by a pentadentate diborate ligand: Interconversion of hydroxo and oxo complexes. (15th March 2020) - Beh, Daniel W.; Piers, Warren E.; Maron, Laurent; Yang, Yan; Gelfand, Benjamin S.; Li, Jian-Bin
Graphical abstract: Hydrolysis of scandium alkyls supported by a dianionic pentadentate ligand to form dimeric hydroxo and oxo complexes, along with further products, is described. Abstract: Uncontrolled reaction of water with scandium alkyls (compounds 1-R ) supported by a dianionic, pentadentate ligand leads to rapid formation of an oxo-bridged dimer (2 ). Solid state samples of 1-CH2 SiMe3 can be exposed to ambient atmosphere to generate samples enriched in the bridging dihydroxo dimer 3, which slowly converts to the μ-oxo species with elimination of water. DFT computations show that 3 is actually more thermodynamically stable than 2, but the reactivity of 3 with the water eliminated leads to its decomposition to 2 and several hydrolysis products. Some of these products were characterized by X-ray crystallography, specifically a hexameric scandium dihydroxo cluster (4 ) in which the pentadentate ligand has partially demetallated. Attempts to synthesize hydroxo complex 3 by protonation of 2 also lead to hydrolysis products.